2013
DOI: 10.1371/journal.pone.0059746
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance on the Status of Immune Cells after Echinnococcus granulosus Protoscoleces Infection in Balb/c Mice

Abstract: BackgroundCystic echinococcosis is a global parasitic disease caused by infection with Echinococcus granulosus larvae with potentially life-threatening complications in humans. To date, the status of the immune cells believed to be associated with the pathogenicity of E. granulosus infection has not been demonstrated clearly.Methodology/Principal FindingsIn this study, we developed a multiplex flow cytometry assay to investigate the systemic immune status of innate and adaptive immunity at 30, 180, 360 days po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 39 publications
1
44
0
1
Order By: Relevance
“…These cells can accumulate in the spleen and in the liver (23). Tregs and MDSCs are also detected in early peritoneal immune responses against experimental E. granulosus infection (6,28). While we did not check the status of MDSCs, high levels of CD4 + lymphocytes, especially the CD25 + CD4 + T cells, were observed in the liver of the mice from the Echinococcus infection and breast cancer group.…”
Section: Discussionmentioning
confidence: 82%
“…These cells can accumulate in the spleen and in the liver (23). Tregs and MDSCs are also detected in early peritoneal immune responses against experimental E. granulosus infection (6,28). While we did not check the status of MDSCs, high levels of CD4 + lymphocytes, especially the CD25 + CD4 + T cells, were observed in the liver of the mice from the Echinococcus infection and breast cancer group.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, PSC present Fc-binding activity (Baz et al 1998) and express immune regulatory antigen B and EgTeg (Ortona et al 2005;Sanchez et al 1991;Monteiro et al 2010). Recently, T-regulatory and myeloid-derived suppressor cells have been found to be systemically expanded in mice with E. granulosus infection and in CE patients (Pan et al 2013;Tuxun et al 2012). Taken together, these results support the presence of an immunomodulatory environment downregulating both Th1 and Th2 responses and favoring parasite survival.…”
Section: Immune Response To E Granulosusmentioning
confidence: 75%
“…Single cell suspensions were prepared from the murine spleens after 8 months of infection with E. granulosus protoscoleces and from normal murine spleens (control group), as published previously [5]. Then, M-MDSCs were collected according to the instructions of the mouse Myeloid-Derived Suppressor Cell Isolation Kit (Miltenyi Biotec, Germany), and the cells were incubated with the following anti-mouse antibodies: PE-Gr-1, FITC-CD11b, APC-Ly-6G and PerCP-Cy5.5-Ly-6C.…”
Section: M-mdsc Isolation and Culturementioning
confidence: 99%
“…The molecular mechanisms underlying its development and pathogenesis are still unclear [1][2][3], although it has been reported that this parasite can successfully escape host immune responses, and a number of immunoregulatory mechanisms related to macrophages and dendritic cells as well as regulatory T cells are potentially involved [2]. In our previous studies, we found that hydatid cysts of E. granulosus could promote the formation of tubes from human umbilical vein endothelial cells (HUVECs) in vitro [4], and that myeloid-derived suppressor cells (MDSCs) were significantly enriched in the spleen and peripheral blood of Balb/c mice infected with E. granulosus and played an immunosuppressive role [5]. The in vitro results are supported by other studies which have shown that angiogenesis is critical for parasites to acquire the nutrients necessary for growth, maturity and breeding after infection [6].…”
Section: Introductionmentioning
confidence: 99%